Dose-dependent effects of curcumin on bacterial growth and sperm quality during refrigerated storage of equine epididymal sperm - Gil, Lydia; González, Noelia; Horndler, Lydia; Luño, Victoria (Frontiers in Veterinary Science, 2026)
Cooling equine sperm for storage can reduce its quality and functional characteristics, presenting challenges for preservation methods. During refrigeration, spermatozoa are exposed simultaneously to oxidative stress and bacterial contamination, both of which compromise sperm viability and fertility potential. To limit bacterial proliferation, commercial extenders are routinely supplemented with antibiotics, but growing concern about antimicrobial resistance has prompted the search for natural alternatives. This study aimed to explore the effects of curcumin, a polyphenolic compound from Curcuma longa with well-documented antioxidant and antimicrobial properties, on refrigerated equine epididymal sperm over 96 h, focusing on its antimicrobial activity and impact on basic sperm quality parameters in an antibiotic-free extender. Sperm samples were collected from 12 stallions and diluted in an antibiotic-free extender containing different concentrations of curcumin: 0 mM (control), 0.125 mM, 0.25 mM, and 0.5 mM. Parameters such as motility, viability, acrosomal integrity, and bacterial growth were evaluated after 1 and 96 h of storage at 4 °C to 6 °C. The results showed no significant effects of curcumin on sperm quality at 1 h. However, after 96 h, higher curcumin concentrations (0.25 and 0.5 mM) reduced motility and viability compared to the control group. Despite this, all tested concentrations significantly inhibited cultivable aerobic bacterial growth after 96 h, with 0.125 mM curcumin offering the most favorable balance between antimicrobial effect and preservation of basic sperm quality parameters. These findings provide preliminary evidence that low concentrations of curcumin may act as a potential complementary or partial alternative to antibiotic use in equine semen extenders, although further studies in ejaculated semen and with more comprehensive functional and microbiological assessments are required before its routine application can be recommended.